Pengembangan Program Rohis (Rohani Islam) di Sekolah Dasar Negeri Bukittinggi - Elvy Gustina; Zulfani Sesmiarni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The gap in Islamic religious education in schools is commonplace, school programs such as extracurricular activities that are formed do not fully provide religious education to children, generally only focusing on cognitive. Currently there is a decline in student character. Of course this must be addressed immediately. The purpose of this study is to develop extracurricular activities of Rohis (Islamic Spirituality) in fostering quality students in knowledge, faith, and charity. This type of research is qualitative with a descriptive approach. Data were obtained from the results of observations, interviews, and documentation supported by sources from journals. The results of the study showed that there were several activities carried out in Rohis activities, Al-Qur'an recitation, charity, sunnah dhuha prayer, congregational zuhur prayer. These activities were carried out in accordance with considerations from the results of interviews and observations and the impacts that would be obtained if the activities were effective. Appropriate methods are needed such as habituation and role models as well as cooperation between parents and the community for the smooth running of the Rohis extracurricular program at Bukittinggi State Elementary School.